Prevalence, diagnostic methods, and clinical outcomes of wasting among paediatric cancer patients in Africa: A systematic review and meta-analysis - Ivaan Pitua; Daisy Wannyana; Derrick Bary Abila; Felix Bongomin (PLoS ONE, 2026)
Background Malnutrition is a prevalent and modifiable co-morbidity in paediatric oncology, yet no comprehensive pan-African synthesis of its burden has been conducted. This systematic review and meta-analysis estimated the pooled prevalence of wasting and acute malnutrition among paediatric cancer patients in Africa, evaluated the impact of diagnostic assessment methods on reported prevalence, and characterised associations with adverse clinical outcomes. Methods We searched PubMed/MEDLINE, EMBASE and Web of Science for observational studies published from January 2000 to December 2025 reporting wasting or acute malnutrition among children and adolescents (0–19 years) with confirmed malignancies in African healthcare settings. Two independent reviewers screened studies, extracted data, and appraised quality using the Joanna Briggs Institute Critical Appraisal Checklist. Pooled prevalence was calculated using a random-effects model with Freeman-Tukey double arcsine transformation. Heterogeneity was assessed using the I ² statistic and Cochran’s Q test. Publication bias was evaluated with Egger’s regression test. Certainty of evidence was assessed using the GRADE framework. Results Sixteen independent cohorts comprising 2,419 paediatric cancer patients across eight African countries were included. The pooled prevalence of wasting or acute malnutrition was 39.7% (95% CI: 30.7%–49.1%), with individual study estimates ranging from 11.7% to 67.6%. Between-study heterogeneity was substantial ( I ² = 95.3%; 95% CI: 92.7%–96.1%, p < 0.001). Studies using mid-upper arm circumference (MUAC) consistently detected substantially higher rates of malnutrition than those relying on weight-for-height or body mass index criteria from the same patient populations. No significant publication bias was detected (Egger’s test p = 0.503). GRADE certainty of evidence was very low, primarily due to heterogeneity. Wasting was independently associated with higher chemotherapy toxicity, treatment-related neutropenia, sepsis, and reduced overall survival across two of the included cohorts. Conclusions Wasting and malnutrition affects about two in five children with cancer in the African countries studied. The diagnostic tool employed is the single most consequential determinant of detected prevalence, and weight-based metrics alone are inadequate in populations with large solid tumours. Universal adoption of MUAC-based screening, structured algorithm-guided nutritional intervention, and integration of socioeconomic vulnerability assessment into routine oncological care are evidence-based priorities for improving treatment tolerability and survival in this population.